Numerical study of dam break waves on movable beds for various forms of the obstacle by VOF method. (1st August 2020) - Issakhov, Alibek; Zhandaulet, Yeldos
Abstract: This paper considered the problem of numerical simulation of an incompressible dam break flow consisting of three phases. The movement of the water free surface is performed using the Newtonian fluid model, and the mud mixture movement is carried out by the non-Newtonian fluid model based on the VOF method. The PISO numerical algorithm was selected as a numerical method for solving equations. This paper discusses the problems of dynamic loads arising from the impact of a dam break flow using numerical modeling. The received computational data are matched with the two experiment results, which allow confirming the behavior of the instantaneous flow and the evolution of pressure at the relative points of the obstacle. The water flow and non-Newtonian fluid for different forms of obstacles were also modeled. It was found that a non-Newtonian fluid rather strongly reduces the maximum shock the pressure value of the water flow. Highlights: The paper presents the Numerical simulation of dam break waves on movable beds for various forms of the obstacle by VOF. . It is solved by the Navier-Stokes, multiphase flow is used Newtonian fluid and non-Newtonian fluid models. . The numerical solution based on the PISO algorithm (Pressure-Implicit with Splitting of Operators) . Numerical modeling of water flow and non-Newtonian fluid for different forms of obstacles were also modeled. .